The state of the cardiovascular system in typhoid fever (Experience of a leading infectious disease specialist of a limited contingent of Soviet troops in Afghanistan) - Yu. I. Ljashenko (Журнал инфектологии, 2022)
In order to clarify the frequency and duration of changes in the functional state of the cardiovascular system in typhoid patients, as well as the definition of the structure and features of injuries in modern conditions, the medical records of 286 patients were analysed retrospectively, including 36 persons with a fatal outcome among members of a limited contingent of Soviet troops in Afghanistan (1983–1985). The results of the tests in the deceased were compared to the autopsy of the tissues of their bodies.The nature of the changes in the indicators of the functional state of the cardiovascular system during various periods of light, medium, heavy and extremely severe forms of typhoid fever and their diagnostic informativeness, structure, as well as the frequency of registration are explained, features of clinical and morphological manifestations of infectious toxicity shock, thrombohemorrhagic syndrome, myocardial dystrophy, infectious toxicity myocarditis, as well as the significance of pre-mortem status in this disease. It has been established that patients with an extremely severe form of relapse of typhoid in connective tissue develop in the intercardiomyocytic intervals.